2018
DOI: 10.1101/254821
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial Tissue Engineering Partially Restores Function after Spinal Cord Injury

Abstract: Hydrogel scaffolds provide a beneficial microenvironment in transected rat spinal cord. A combinatorial biomaterials based strategy provided a microenvironment that facilitated regeneration while reducing foreign body reaction to the 3-dimensional spinal cord construct. We used poly lactic-co-glycolic acid microspheres to provide sustained release of rapamycin from Schwann cell (SC)-loaded, positively charged oligopolyethylene glycol fumarate scaffolds. Three dose formulations of rapamycin were compared to con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…We have previously demonstrated that the use of OPF+ scaffolds containing rapamycin eluting microspheres were able to reduce the fibrotic reaction and improve functional motor recovery over 6 weeks (17). Here we sought to investigate the relationship of regenerating axons to the vasculature through OPF+ scaffolds containing Matrigel only (MG), Schwann cells only (SC), or Schwann cells with rapamycin (RAPA).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously demonstrated that the use of OPF+ scaffolds containing rapamycin eluting microspheres were able to reduce the fibrotic reaction and improve functional motor recovery over 6 weeks (17). Here we sought to investigate the relationship of regenerating axons to the vasculature through OPF+ scaffolds containing Matrigel only (MG), Schwann cells only (SC), or Schwann cells with rapamycin (RAPA).…”
Section: Resultsmentioning
confidence: 99%
“…Scaffolds loaded with rapamycin-releasing microspheres were previously found to promote peripheral nerve regeneration when implanted in the early phase of sciatic nerve injury (32). Our lab has previously demonstrated that administration of rapamycin resulted in improved functional recovery following spinal cord transection, which was linked to improved axonal regeneration, possibly through increased BDNF and GDNF secretion of transplanted SCs (17). Although rapamycin was found to promote secretion of nerve growth factors, and has been suggested for application in peripheral nerve regeneration therapy (33, 34), our study found a significantly greater number of myelinated and unmyelinated axons per channel in the SC group, which were more clustered compared to the MG and RAPA group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This regeneration can be further improved by loading the channels with GDNF-secreting Schwann cells, leading to modest functional recovery [5]. We have also shown that the OPF+ material can be modified by incorporating the anti-fibrotic drug rapamycin in PLGA microspheres [27]. OPF+ multichannel scaffolds containing rapamycin microspheres were also combined with Schwann cells to help promote functional recovery following SCI.…”
Section: Discussionmentioning
confidence: 99%